Resposta dos pequenos agricultores a estímulos de preço - Almada Cruz , Tancredo; Barbosa , Túlio; Batista de Oliveira , Evonir; Aureliano Teixeira , Juraci (Revista Ceres, 2025)
This study attempts to obtain empirical knowledge about the behavior of subsistence farmers when they face price (of product) stimuli.